1997
DOI: 10.1007/s002560050238
|View full text |Cite
|
Sign up to set email alerts
|

Anteroinferior tears of the glenoid labrum: fat-suppressed fast spin-echo T2 versus gradient-recalled echo MR images

Abstract: Observer 1 had a sensitivity of 0.56 on the GRE images and 0.67 on the FSE images (P > 0.5), with a specificity of 1.0 for both sequences. Observer 2 had a sensitivity of 0.78 and a specificity of 0.89 for both sequences. In this small study there is no significant difference between GRE and fat-suppressed FSE images in their ability to diagnose anteroinferior labral tears. When evaluating the labrum with conventional MRI, axial fat-suppressed FSE T2-weighted images can be used in place of GRE images without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In the past, 3D T 2 *-weighted GRE sequences have been used to evaluate the shoulder joint; they exhibited similar sensitivity and specificity values for detecting RCT and labral tears, relative to 2D spin-echo sequences, and demonstrated much shorter acquisition times. [35][36][37] However, the recent use of TSE sequences has significantly reduced the time required to obtain images with intermediate-weighted and T 2 -weighted contrast; thus, TSE sequences are currently the sequences of choice for evaluation of the shoulder joint. 8,11 Moreover, Lee et al 41 demonstrated that insensitivity to surgical materials is one of the strengths of a TSEbased MR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, 3D T 2 *-weighted GRE sequences have been used to evaluate the shoulder joint; they exhibited similar sensitivity and specificity values for detecting RCT and labral tears, relative to 2D spin-echo sequences, and demonstrated much shorter acquisition times. [35][36][37] However, the recent use of TSE sequences has significantly reduced the time required to obtain images with intermediate-weighted and T 2 -weighted contrast; thus, TSE sequences are currently the sequences of choice for evaluation of the shoulder joint. 8,11 Moreover, Lee et al 41 demonstrated that insensitivity to surgical materials is one of the strengths of a TSEbased MR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, external rotation may result in a more flat labrum. A thinner or even absent labrum may be an age-related degenerative change, but can also be associated with instability [ 1 2 3 4 5 6 7 8 9 10 11 12 13 ].…”
Section: The Labrummentioning
confidence: 99%
“…In the past, 3D T2*-weighted gradient-echo sequences have been used to evaluate the shoulder joint with similar sensitivity and specificity values for detecting rotator cuff and labral tears as 2D spin-echo sequences and much shorter acquisition times (74)(75)(76). However, over the past decade the use of fast spin-echo sequences have significantly reduced the time required to obtain images with intermediate-weighted and T2-weighted contrast.…”
Section: Shoulder Joint Imagingmentioning
confidence: 99%